Study of hydrologically critical subbasins under climate change - Gaur S.; Kumar R.; Ohri A.; Mishra S.; Gond A.K.; Dwivedi S.B.; Jha M.; Chaturvedi A.; Singh B.N. (My University, 2025)
This study aims to evaluate the impact of climate change on the surface water hydrology of the Gopad river basin in India. The outputs of four CMIP6 Global Climate Models have been downscaled using the statistical downscaling method to the basin level. A comparative analysis for the accuracy achieved in the bias correction for the combination of GCM and downscaling method has been performed before utilising the downscaled weather parameters for hydrological study. The MIROC6 and ACCESS-CM2 were found best for the simulation of precipitation and temperature, respectively. The Distribution Mapping and Variance Scaling methods have shown better accuracy w.r.t other statistical methods. The impact of climate change has been found significant since the temperature has been observed to be increased by 3.16 °C by the end of 2060; meanwhile, there is an average decrease of 9.2% in the annual rainfall from the baseline. The peak runoff has increased while there is a significant decrease in the groundwater recharge. Further, hydrologically critical subbasins (HCS) have been delineated based on the runoff, groundwater recharge, and baseflow. Most HCS was observed to be situated in the upper Gopad river basin, representing the area’s pristine conditions. © 2023 The Authors.